Roy Sievers : "the sweetest right handed swing" in 1950s baseball - Scimonelli, Paul, 1949- (McFarland and Company, Inc., 2018)
"Few players in the history of baseball suffered as many professional setbacks as Roy Sievers (1926-2017). After an award winning rookie season, he endured a year and a half-long slump, a nearly career-ending injury and a major position change. Traded in 1954, he prevailed and became one of the most feared hitters of the decade"--